Efek Larvasida Ekstrak Tegates erecta Fraksi Heksan dan Aseton terhadap Larva Nyamuk Aedes aegypti Instar 3 dan 4 - November Rianto Aminu; Hartati Soetjipto; A Ign Kristijanto (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Resistance to temephos as a larvicide of A. aegyptimosquitoes has occurred in Indonesia. Therefore, it is necessary to look for other active compounds that can act as larvicides, but also environmentally friendly. This study used leaf and roots extract of T. erectahexane and acetone fraction as larvicide. The process begins with drying followed by extracting samples (leaves and roots of T. erecta) each with hexane and acetone solvents. Test solutions were made with a concentration of 0, 0.0075, 0.015, 0.03, and 0.1% (w/v) of the extract produced. Larvicide test was carried out referring to WHOPES by observing the mortality of instar larvae 3 and 4 in each extract. The results obtained showed the mortality percentage of larvae increased with increasing concentration and exposure time in both types of larvae. The lowest LC 50 was obtained from the root extract of hexane fraction (37 ppm) for 3rd instar larvae and acetone fraction (61 ppm) for instar 4 larvae. Keywords: Larvae, A. aegypti, T. erecta. Fraction